Textbook as an Injustice: Analysis of Textbooks used in Teaching at Primary Schools of Lakshadweep - Ali Mubarak. B.B AND Amruth G Kumar (International Journal of Research and Analytical Reviews, 2018)
Primary school students of Lakshadweep learn things about an unfamiliar socio-cultural milieu by neglecting their own socio-cultural environment. The complexities in the content would in fact badly influence the effective learning process and this kind of socially and culturally irrelevant learning process would give them a threat of a stigmatized and inferior cultural identity. This paper unveils the pedagogical injustice by analyzing the content of the textbooks used for teaching at primary level in Lakshadweep. This paper argues that culturally unfamiliar content in the textbooks and its teaching would lead to a ‘cultural conflict’ in the minds of primary school students, eventually leading to a ‘culture shock’. This ‘shock’ leads to the ‘devaluation’ of the culture in which they are born and brought up.